Low cardiorespiratory fitness and obesity for ADHD in childhood and adolescence: A 6‐year cohort study. (8th January 2021) - Muntaner‐Mas, Adrià; Ortega, Francisco B.; Femia, Pedro; Kiive, Evelyn; Eensoo, Diva; Mäestu, Jarek; Franke, Barbara; Reif, Andreas; Faraone, Stephen V.; Harro, Jaanus
Abstract : Attention‐deficit/hyperactivity disorder (ADHD) is a prevalent disorder in childhood and identifying risk factors associated with developing ADHD during childhood and adolescence is relevant from a clinical and epidemiological point of view. This work examines (a) whether overweight/obesity and low cardiorespiratory fitness (CRF) are associated with increased ADHD symptoms in childhood (cross‐sectional analysis), and (b) whether overweight/obesity and low CRF levels during childhood predict increased ADHD symptoms in adolescence (longitudinal analysis). Data were examined from a longitudinal study of Estonian inhabitants who took part in the European Youth Heart Study (EYHS) in 1998 and 1999 (baseline age 9 years), who were re‐evaluated 6 years later as part of the longitudinal Estonian Children Personality Behaviour and Health Study (ECPBHS). CRF was determined via an incremental maximal cycle‐ergometer test, overweight/obesity was based on body mass index (BMI), and the 7‐point af Klinteberg Hyperactivity Scale was used to assess ADHD symptoms at both time points. In the cross‐sectional analysis, children with overweight/obesity were at greater risk of ADHD symptoms compared to underweight/normal weight children, as were those unfit compared to fit children (OR = 1.92 and 95%CI = 1.02‐3.55, and OR = 1.84 and 95%CI = 1.13‐2.98, respectively). The cross‐sectional association between BMI and ADHD symptoms was mediated by CRF ( z  = 2.116, 42.9%; P  = .034). The longitudinal analysis showed being unfit in childhood was associated with a greater risk of increased ADHD symptoms 6 years later in adolescence (OR = 2.26 and 95%CI = 1.14‐4.47), even after adjusting for baseline ADHD symptoms and BMI. Our result suggests that being unfit is an additional risk factor for increased ADHD symptoms during childhood and adolescence. The association between BMI and ADHD symptoms was mediated by CRF in the cross‐sectional analysis, and no association was seen between overweight/obesity and increased ADHD symptoms.